Are current theories of panic falsifiable? [article]. - Roth, W. T.
The authors examine 6 theories of panic attacks as to whether empirical approaches are capable of falsifying them and their heuristic value. The authors conclude that the catastrophic cognitions theory is least falsifiable because of the elusive nature of thoughts but that it has greatly stimulated research and therapy. The vicious circle theory is falsifiable only if the frightening internal sensations are specified. The 3-alarms theory postulates an indeterminate classification of attacks. Hyperventilation theory has been falsified. The suffocation false alarm theory lacks biological parameters that unambiguously index dyspnea or its distinction between anticipatory and panic anxiety. Some correspondences postulated between clinical phenomena and brain areas by the neuroanatomical hypothesis may be falsifiable if panic does not depend on specific thoughts. All these theories have heuristic value, and their unfalsifiable aspects are capable of modification. -- (from the author)
Keywords: Review; Panic; Theory; Falsifiability; Cognition; Respiration; Neuroanatomy